The homeostatic dynamics of feeding behaviour identify novel mechanisms of anorectic agents - McGrath,T; Spreckley,E; Rodriguez,A; Viscomi,C; Alamshah,A; Akalestou,E; Murphy,K; Jones,N (PLoS Biology, 2019)
Better understanding of feeding behaviour will be vital in reducing obesity and metabolic syndrome, but we lack a standard model that capturesthe complexity of feeding behaviour. We construct an accurate stochasticmodel of rodent feeding at the bout level in order to perform quantitativebehavioural analysis. Analysing the different effects on feeding behaviour ofPYY3-36, lithium chloride, GLP-1 and leptin shows the precise behaviouralchanges caused by each anorectic agent. Our analysis demonstrates that thechanges in feeding behaviour evoked by the anorectic agents investigated donot mimic the behaviour of well-fed animals, and that the intermeal intervalis influenced by fullness. We show how robust homeostatic control of feedingthwarts attempts to reduce food intake, and how this might be overcome. Insilico experiments suggest that introducing a minimum intermeal interval ormodulating upper gut emptying can be as effective as anorectic drug administration.